Between Tradition and Modernity: Social Responses to Infrastructure Development in Maros Regency - Sumandiyar, Adi; Irwan (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
Infrastructure development in buffer zones such as Maros Regency of Indonesia’s Sulawesi Island presents a dilemma between the push for modernization and the preservation of local traditional values. Amid the rapid expansion of roads, bridges, and tourism projects, local communities face disruptions to the social, cultural, and economic spaces that have long sustained their way of life. This study aims to analyze the social responses of the Maros community to infrastructure development, particularly in the context of the tension between tradition and modernity. A qualitative approach was employed, using an exploratory case study design conducted in three villages: Jenetaesa, Tukamasea, and Salenrang. Data were collected through in-depth interviews, participant observation, and local documentation, and analyzed using Pierre Bourdieu’s theories of habitus and social fields. The findings reveal that development has led to the transformation of symbolic spaces, shifts in power relations, and the emergence of unequal access to development benefits. Community responses vary, including forms of cultural resistance, conditional social negotiation, and hybridization between traditional values and modern elements. This study concludes that technocratic development, when lacking cultural sensitivity, poses a threat to social cohesion. Therefore, sustainable development in local contexts requires a participatory approach that recognizes communities as active agents in shaping the direction of change.